The role of exosomal miRNA-125b derived from colon cancer-associated fibroblasts in skeletal muscle cachexia - Ho Seung Kim; Jinsu Kim; Bom Lee; Yonghyun Lee; So-Yeon Park; Bo-Young Oh; Kyung-Ah Cho; Soon Sup Chung; Gyoung Tae Noh (PLoS ONE, 2026)
Cancer-associated cachexia is a multifactorial syndrome characterized by significant weight loss, primarily due to skeletal muscle atrophy. This condition impairs the quality of life and survival of patients with cancer. Although the mechanisms underlying cancer-associated cachexia, including exosomes and microRNAs (miRNAs), have been extensively explored, research specifically focusing on cancer-associated fibroblast (CAF)-derived exosomes is lacking. Therefore, in this study, we evaluated the effects of CAF-derived exosomal miRNAs from colon cancer on skeletal muscles using the Human Skeletal Muscle (HSkM) cell line. CAF-derived exosomes were isolated from colon cancer samples, and their effects on cell morphology were analyzed using confocal microscopy. The results indicate that treatment with CAF-derived exosomes significantly reduced myosin diameter. Moreover, miRNA sequencing revealed that miR-125b was enriched in CAF-derived exosomes. HSkM cells were subsequently transfected with a miR-125b mimic, which significantly reduced myosin diameter. Notably, co-treatment with CAF-derived exosomes and an miR-125b inhibitor reversed this effect. In conclusion, this study demonstrates the potential role of CAF-derived exosomes and miR-125b in cancer-associated cachexia, offering insights into the contribution of the tumor microenvironment and suggesting possible therapeutic targets.